The level and distribution of the GABABR1 and GABABR2 receptor subunits in the rat's inferior colliculus - Jamal, Lena; Khan, Aziz N.; Butt, Sehrish; Patel, Chirag R.; Zhang, Huiming (Frontiers in Neural Circuits, 2012)
The type B γ-aminobutyric acid receptor (GABAB receptor) is an important neurotransmitter receptor in the midbrain auditory structure, the inferior colliculus (IC). A functional GABAB receptor is a heterodimer consisting of two subunits, GABABR1 and GABABR2. Western blotting and immunohistochemical experiments were conducted to examine the expression of the two subunits over the IC including its central nucleus, dorsal cortex, and external cortex (ICc, ICd, and ICx). Results revealed that the two subunits existed in both cell bodies and the neuropil throughout the IC. The two subunits had similar regional distributions over the IC. The combined level of cell body and neuropil labelling was higher in the ICd than the other two subdivisions. Labelling in the ICc and ICx was stronger in the dorsal than the ventral regions. In spite of regional differences, no defined boundaries were formed between different areas. For both subunits, the regional distribution of immunoreactivity in the neuropil was parallel to that of combined immunoreactivity in the neuropil and cell bodies. The density of labelled cell bodies tended to be higher but sizes of cell bodies tended to be smaller in the ICd than in the other subdivisions. No systematic regional changes were found in the level of cell body immunoreactivity, except that GABABR2-immunoreactive cell bodies in the ICd had slightly higher optic density than in other regions. Elongated cell bodies existed throughout the IC. Many labelled cell bodies along the outline of the IC were oriented in parallel to the outline. No strong tendency of orientation was found in labelled cell bodies in ICc. Regional distributions of the subunits in ICc correlated well with inputs to this subdivision. Our finding regarding the contrast in the level of neuropil immunoreactivity among different subdivisions is consistent with the fact that the GABAB receptor has different pre- and postsynaptic functions in different IC regions.